The effects of shared medical appointment multidisciplinary interventions for non-organic feeding disorders in infants and young children during the self-feeding transition period - Chen, Die; Peng, Wen-Tao; Liu, Xiao-Mei; Xiong, Fei; Luo, Yu; Luo, Hong; Tang, Meng-Yan; Guo, Xin-Yu; Fu, Xiao; Feng, Qian; Chen, Hong (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to implement shared medical appointment multidisciplinary interventions for non-organic feeding disorders in infants and young children and evaluate their effects.MethodsA total of 52 children aged 6–24 months and their respective feeders were included in the study. Of them, 26 were classified into the intervention group, and 26 were classified into the control group. Routine child health care measures were applied to the control group. The child health care measures combined with shared medical appointment multidisciplinary interventions, including 3 collective interventions and 3 months of follow-up, were applied in the intervention group. Data concerning physical growth indicators, Montreal Children's Hospital Feeding Scale (MCH-FS) scores, Infant and Child Feeding Index (ICFI) scores, and Self-Rating Anxiety Scale (SAS) scores in the two groups were collected.ResultsDue to insufficient participation in interventions, loss of follow-up, and withdrawal from the study, 46 cases were finally included in this study, with 23 cases in each group. The physical growth indicators in the intervention group were better than the control group, with the effects of time. The intervention group had lower MCH-FS score, higher ICFI score and lower SAS score.ConclusionsThese results provide preliminary evidence of the effectiveness and feasibility of shared medical appointment multidisciplinary interventions, which help promote feeding and physical growth in infants and young children and provide a reference for improving management for feeding in infants and young children.